If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + 63 = 13x + -65 Reorder the terms: 63 + 25x = 13x + -65 Reorder the terms: 63 + 25x = -65 + 13x Solving 63 + 25x = -65 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 63 + 25x + -13x = -65 + 13x + -13x Combine like terms: 25x + -13x = 12x 63 + 12x = -65 + 13x + -13x Combine like terms: 13x + -13x = 0 63 + 12x = -65 + 0 63 + 12x = -65 Add '-63' to each side of the equation. 63 + -63 + 12x = -65 + -63 Combine like terms: 63 + -63 = 0 0 + 12x = -65 + -63 12x = -65 + -63 Combine like terms: -65 + -63 = -128 12x = -128 Divide each side by '12'. x = -10.66666667 Simplifying x = -10.66666667
| 5y-11=44 | | 3+3d=12 | | 3=9-2r | | 3(x-1)+4=2x | | P-4=1+3p+3p | | cos^2x+sin^2x= | | 2a+15=3a-18 | | (-4m^2+3n^2-5n)-[(3m^2-5n^2+2n)+(-3m^2)+4n^2]= | | -sin^2x+cos^2x= | | 2x+15+3x+5=6x-37 | | 9x+729=0 | | M=yi | | 10x-12=3x+11 | | -5x-10=q | | 2w^2+21w-180=0 | | b^-2/b^4 | | 8z^2-3z-5z^2-4z= | | 9x-2=-3 | | Z-z-z+z= | | 7x+5-5x=-11-6x | | (5x+3)(2x+25)=1406 | | 3x-5=-8(5n+6) | | 25x-14+7x+2=180 | | X-.25x=840 | | x+-6x-3=30 | | X+1200=8500 | | 3p^4+5p^4-2p^4= | | 13x-7+8x-2=180 | | (13x-6)-3=100-18 | | N^2+10n-62=0 | | 8x-16=6x+20 | | 10x-13=37+20(2) |